Development and Validation of analytical method for Anticancer drug Cyclophosphoamide by UPLC - Limani, Gunjan; Chauhan, Janvi; Hafeez, Hajera; M Chavan, Ghanshyam; Shyamala, Shyamala; Jhansipriya, M.V.; Kumar Reddy, Boi Basanta; Meharaj, S. K.; Pal, Rishi (Journal of Neonatal Surgery, 2025)
Cyclophosphamide can be quantified in tablet formulations using the approved Stability Indicating RP-UPLC method, which is simple, quick, accurate, and specific. At the LOQ level, the average recovery for Cyclophosphamide is 95.0%, 90.6%, 86.8%, and 88.7%; for Related compound-A, it is 99.7%, 95.6%, 92.0%, and 94.2% at the LOQ level; for Related compound-B, it is 100.5%, 96.0% at the 50% level, 109.9% at the 100% level, and 88.2% at the 150% level; and for Related compound-D, the LOQ level is 102.8%, 50% is 98.7%, at 100% is 94.9%, and at 150% level is 97.7%. Cyclophosphamide's overall percentage RSD is 3.07, whereas related molecule A, B, and C have respective RSDs of 2.77, 7.76, and 5.29.